(3GdZQI GdZQGA aj JHQjQ eYGde GdGgJOGAs - (3GdbRhjfj, GdMGFQj, GdTjQGRj, eMeO MSf Hf eMeO eYUhe, J (B1240 (3g`s ((3eMeO Yj Hf GdYHO Gdedi GdMhFj GdMGFQjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj HOC Ndb GdEfSGf ef Wjf Ke LYd fSdg ef SdGdI ef eGA egjf (B... (3CQOJ Cf GcJH cJGHG jMJhj Ydi NdGUI eG jfJaY Hg Chdh GdCdHGH ef cdGe CSGWjf GdMceI hCNHGQ GdYJQI GdCWjGH (B....s
(3BNQgG (B:s
... (3hbO JbOe ef CMcGe GdUMHI hBOGH GdENhI eG jZfjc Ef cfJ WGdHG hdfbWY GdcdGe Ydi MH Gddg hQShdgs
(3JHUQI GdYfhGf (B:s
(3hjSei (B: (3GdZQI GdZQGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\92s
(3GdPQjYI (B18 - 31 (612)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds